2020
DOI: 10.1101/2020.03.09.983106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Axial skeleton anterior-posterior patterning is regulated through feedback regulation between Meis transcription factors and retinoic acid

Abstract: Vertebrate axial skeletal patterning is controlled by coordinated collinear expression ofHox genes and axial level-dependent activity of Hox protein combinations. Transcription factors of the Meis family act as cofactors of Hox proteins and profusely bind to Hox complex DNA, however their roles in mammalian axial patterning have not been established. Similarly, retinoic acid (RA) is known to regulate axial skeletal element identity through the transcriptional activity of its receptors, however whether this rol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Indeed, putative enhancer regions identified in pSHF cells revealed enrichment for HOX and TALE binding motifs ( Stefanovic et al., 2020 ). While HOX and MEIS genes appear to be direct targets of RA itself ( Mercader et al., 2000 ; Berenguer et al., 2020 ), studies have shown that they can also regulate Raldh2 expression and thereby RA levels through a positive feedback loop ( Vitobello et al., 2011 ; López-Delgado et al., 2021 ). Interestingly, misexpression of Hoxb1 in the aSHF domain resulted in an upregulation of Tbx5 and Nr2f2 ( Stefanovic et al., 2020 ), both of which are implicated in the differentiation of atrial and sinoatrial nodal cells in vivo and in vitro ( Liberatore et al., 2000 ; Wu et al., 2013 ; Devalla et al., 2015 ; Protze et al., 2017 ).…”
Section: Ra In Atrial Developmentmentioning
confidence: 99%
“…Indeed, putative enhancer regions identified in pSHF cells revealed enrichment for HOX and TALE binding motifs ( Stefanovic et al., 2020 ). While HOX and MEIS genes appear to be direct targets of RA itself ( Mercader et al., 2000 ; Berenguer et al., 2020 ), studies have shown that they can also regulate Raldh2 expression and thereby RA levels through a positive feedback loop ( Vitobello et al., 2011 ; López-Delgado et al., 2021 ). Interestingly, misexpression of Hoxb1 in the aSHF domain resulted in an upregulation of Tbx5 and Nr2f2 ( Stefanovic et al., 2020 ), both of which are implicated in the differentiation of atrial and sinoatrial nodal cells in vivo and in vitro ( Liberatore et al., 2000 ; Wu et al., 2013 ; Devalla et al., 2015 ; Protze et al., 2017 ).…”
Section: Ra In Atrial Developmentmentioning
confidence: 99%
“…It is also important to note that many domains of meis expression do not overlap with hox expression, as illustrated by expression in anterior regions, such as the midbrain and PA1. Furthermore, in gnathostomes meis genes have also been shown to display hox-independent functions (Lopez-Delgado et al, 2021;Moens and Selleri, 2006), suggesting that the expression domains in lamprey which do not overlap with hox expression are associated with other roles in embryonic and tissue development. Future functional perturbation studies will be required to address the nature of meis gene functions in the pharynx and potential regulatory interactions with Hox genes and other factors.…”
Section: Meis Gene Expression In Relation To Hox Genesmentioning
confidence: 99%
“…Meis proteins are a highly conserved family of transcription factors that have key roles in many aspects of embryonic and axial patterning across metazoans (Burglin, 1997;Lopez-Delgado et al, 2021). In vertebrates, this includes roles in the gene regulatory networks involved in specifying anterior-posterior (A-P) patterning in the developing hindbrain and cranial neural crest (NC) via the clustered Hox genes (Choe et al, 2014;Choe et al, 2009;Choe et al, 2002;Deflorian et al, 2004;Machon et al, 2015;Moens and Selleri, 2006;Stedman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top regulons of this analysis revealed active transcription factors underlying myogenic and non-myogenic cell fates in the EOM at E11.5. Notably, Myf5, Pitx1, Mef2a and Six1, transcription factors known to be implicated in myogenic development (Buckingham and Rigby, 2014), appeared among the top regulons in myogenic cells whereas Fli1, Ebf1, Ets1, Foxc1, Meis1 and Six2, genes known for their involvement in adipogenic, vascular, mesenchymal and tendon development (Jimenez et al, 2006;López-Delgado et al, 2020;Noizet et al, 2016;Truong and Ben-David, 2000;Whitesell et al, 2019;Yamamoto-Shiraishi and Kuroiwa, 2013), constituted some of the highly active non-myogenic transcription factors (Figure 5B). Given that Myf5 appeared as a top regulatory factor of the myogenic program, we interrogated the fate of Myf5-expressing progenitors in a Myf5 nlacZ/nlacZ null genetic background.…”
Section: Obstructing Myogenesis Expands Connective Tissue Formation From Bipotent Cellsmentioning
confidence: 99%